2021
DOI: 10.3390/ijerph182111342
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Ototoxicity Monitoring for Drug-Resistant Tuberculosis in South Africa: An Evaluation Study

Abstract: In response to the drug-resistant tuberculosis (DRTB) ototoxicity burden in South Africa, ototoxicity monitoring has been decentralised, with community health workers (CHWs) acting as facilitators. This study describes a community-based ototoxicity monitoring programme (OMP) for patients with DRTB. Findings are compared to the recommended guidelines for ototoxicity monitoring, the OMP protocol and published studies. This was a retrospective study of longitudinal ototoxicity monitoring of 831 patients with DRTB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As clear as this goal is, achieving it is not easy and has been met by numerous challenges. Evidence suggests that this failure is because of the lack of South African standardised investigative methods and ototoxicity monitoring practises, as well as an absence of a South African government mandate (Khoza-Shangase 2010aStevenson et al 2021).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As clear as this goal is, achieving it is not easy and has been met by numerous challenges. Evidence suggests that this failure is because of the lack of South African standardised investigative methods and ototoxicity monitoring practises, as well as an absence of a South African government mandate (Khoza-Shangase 2010aStevenson et al 2021).…”
Section: Contextmentioning
confidence: 99%
“…As far as the capacity versus demand challenge is concerned, the use of trained nonaudiological screeners (paraprofessionals) to implement OMPs adhering to recommended guidelines should be seriously considered. In a recent retrospective record review study by Stevenson et al (2021), an OMP conducted by CHWs was found to be limited as it fell short of meeting recommended guidelines such as performance of baseline measures, conducting repeated measures at recommended intervals and timeframes, inclusion of ultra high-frequency (UHF) measures, and other important recommendations, including efficient record-keeping that is crucial in an OMP. The author believes that this could have been because of the lack of training of CHWs and the lack of audiologists' involvement in the running and management of the programme that has been raised about this particular programme.…”
Section: Solutions and Recommendationsmentioning
confidence: 99%
“…The data collection procedure for this study was the same as for the larger study (Stevenson et al, 2021). The OMP protocol implemented at the time of data collection was as follows: all patients who received ototoxic medication for treatment of DRTB were identified and referred by their managing doctor and included in the OMP as part of the package of care.…”
Section: Data Collection Proceduresmentioning
confidence: 99%